Infection of BALB/c mice with the filarial nematode Litomosoides sigmodontis: role of CD4+ T cells in controlling larval development. - Al-Qaoud, K M (1997)
Litomosoides sigmodontis is the only filaria which develops from infective larvae into adults in immunocompetent laboratory mice. Depletion of CD4+ T cells from infected BALB/c mice resulted in worm and microfilarial burdens significantly higher than those of infected controls. Th2 cytokines, eosinophilia, and immunoglobulin E, which were strongly induced in infected controls, were diminished in CD4-depleted mice.